Wind environment evaluation on major town of Malaysia - Hafezatul Rasyidah, Othman (2010)
This study focus on wind flow or wind environment of residential areas in Peninsular Malaysia, Sabah and Sarawak. Natural wind flow is one of the most effective methods to help achieve the energy saving in large cities especially under the tropical climate like Malaysia. The weather in Malaysia is characterized by four monsoon regimes, namely, the southwest monsoon, northeast monsoon and two shorter periods of inter-monsoon seasons. For this study, the data of wind velocity in twentytwo (22) weather station in Malaysia obtained from Meteorological Department and considered in wind environment evaluations. Then that data of wind velocities will convert to 1.5 in height at all measuring points were calculated by using the law. The result compared by Table 2.2 in previous researches (Kubota and Miura et al., 2002). From the study, it was found out, in Malaysia there are only two type of wind. First type is weak wind means that area are discomfort thermal and the second type is comfort range to strong wind means that area are comfort thermal. The minimum value of mean wind speed from 2005 to 2009 is O.mis in mean temperature is over 2C at Sitiawan. For the maximum value of mean wind speed is I .7m/s in average value of mean temperature is 276C at Mersing. Base on results, it can be concluded that when considering wind flow at a residential area, terrace housing is not a suitable option for towns located on the south of the Peninsular. It was prefer for high-rise building because it was considered this location of towns was weak wind condition. On the other hand, the major towns exclude the south of the Peninsular including Sabah and Sarawak, they was under the comfort thermal. So, terrace housing or high-rise building is suitable option.